Efektivitas Metode at-Tartil dalam Pembelajaran Tahsin al-Qur’an Mahasiswa Perguruan Tinggi Keagamaan Islam di Kalimantan Timur - Rumainur, Rumainur (LP2M IAIN Samarinda, 2019)
The at-tartil method is a guidebook in learning to read al-quran directly (without spelling) and enter or practice the reading of tartil in accordance with the rules of ulumut tajwid and ulumul ghorib This At-tartil book emerged because it was motivated by unrest among the NU Sidoarjo scholars more precisely the NU Syuriah Branch of Sidoarjo, because at the beginning of the 80-90s various kinds of books were studied in the Koran but not accompanied by the teachers skills in operating books the book. This At-Tartil Method uses a drill technique. The type of research that will be used in this study is to use the Posttest Only method. This study involved two groups, namely the experimental group and the control group, both of whom received the same learning treatment process in terms of content, purpose and teaching material. Referring to the results of data analysis from the results of the research that has been done, obtained t-count value of 22.0503 and t_table value of 1.684. This means that t count> t table then Ho is rejected; Ha accepted. It can be stated that the experimental group and the control group have significant average differences, with this indicating that the use of the At-Tartil method is effective in the learning of PTKI Tahsin Al-Qur'an students in East Kalimantan.